Pengembangan Kapasitas Guru dalam Meningkatkan Kinerja di MAN 2 Lombok - Yusri, Muhammad; Al Idrus, S. Ali Jadid; Fakhri, Moh. (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Teacher capacity building is a continuous effort to improve one's ability to improve their performance. Capacity building is considered effective if it can improve performance. However, if the performance produced is not optimal, capacity development is still needed. This study aimed to determine and analyze teacher capacity building to improve their performance at MAN 2 East Lombok. This study uses a qualitative method, and the data sources of this study include the principal, vice principal, and several teachers, as well as documentation such as the profile of MAN 2 East Lombok and academic supervision. This study collected data through interviews, observations, and documentation. Data analysis involved the processes of reduction, delivery, verification, and drawing conclusions. The results of the study showed that: 1) Increasing teacher capacity at MAN 2 East Lombok was carried out well by emphasizing capacity building at the individual, institutional, and system levels; 2) Increasing teacher performance can be seen in teacher tasks and functions, such as planning and implementing learning and evaluating learning.